Tooth fragment lodged in the upper lip after traumatic dental injury: An unusual case report [Fragment zuba u gornjoj usni nakon dentalne traume: Opis neobičnoga kliničkog slučaja] - (:unkn) unknown (My University, 2011)
Dental fractures are common trauma complications in the oral cavity. When a patient has a laceration in the upper lip and dental trauma to the anterior dentition, an embedded tooth fragment should be suspected. A 10-year old boy was referred to the Department of Pediatric Dentistry, Dental School, Marmara University, Istanbul with a swollen lip, showing local edema and trauma to the maxillary left central incisor. A thorough intraoral examination revealed a fracture of the permanent left maxillary central incisor involving the enamel and dentin without pulp exposure while carefully palpating the tissues of the upper lip; the presence of a foreign body was felt. This was confirmed by a panoramic radiograph and it showed a radiopaque material, similar to the coronal fragment of the fractured incisor. The coronal fragment of the maxillary left central incisor was surgically removed. The fractured tooth was temporarily restored. After two weeks, the tooth was restored with the fragment using the adhesive technique. A thorough clinical examination with soft-tissue radiographs could provide an early diagnosis and indicate surgical removal.
Keywords: Dental restoration; Lip; Tooth fractures; Tooth injuries